2011
DOI: 10.1186/1749-8090-6-96
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent pericardial effusion after cardiac surgery: the use of colchicine after recalcitrant conventional therapy

Abstract: Pericardial effusion represents a common postoperative complication in cardiac surgery. Nonetheless, it can be resistant to conventional therapy leading to prolonged in-hospital stay and worsening of clinical conditions.Recent literature shows that colchicine therapy should be useful in the treatment of recurrent post surgical pericardial effusion.Hereby we report the case of a patient with postsurgical recurrent effusion treated with colchicine, and a review of literature concerning the use of this old drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…The latter comprising complete heart block, which occurred in a child with Down syndrome after AV canal repair. This is consistent with earlier observation that heart block can occur after cardiac surgery for some lesions including AV canal defect, TOF and VSD [21][22][23][24][25][26][27][28][29]. A plausible explanation is that these defects tend to be closely related to the conduction system, which easily gets damaged during cardiac surgery [21,26,29].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The latter comprising complete heart block, which occurred in a child with Down syndrome after AV canal repair. This is consistent with earlier observation that heart block can occur after cardiac surgery for some lesions including AV canal defect, TOF and VSD [21][22][23][24][25][26][27][28][29]. A plausible explanation is that these defects tend to be closely related to the conduction system, which easily gets damaged during cardiac surgery [21,26,29].…”
Section: Discussionsupporting
confidence: 90%
“…Its occurrence has been attributed to a number of factors including surgical and/or microvascular bleeding, epicardial tear with bleeding during pacing wire removal, postoperative anticoagulation, hypoalbuminemia and surgery-induced inflammatory reaction of the pericardium among others [24]. Complete resolution of the effusion following conventional treatment is the norm; but occasionally it may become persistent and/or recurrent, or even progressed to life-threatening cardiac tamponade, requiring invasive therapy [25].…”
Section: Discussionmentioning
confidence: 99%
“…Colchicine is a tricyclic alkaloid agent, and its analgesic and anti-inflammatory effects have been linked to its ability to bind with tubulin, inhibiting neutrophil motility and activity, leading to a net anti-inflammatory effect. The essential antiinflammatory mechanism of colchicine is via the inhibition of granulocyte migration into the inflamed area, thereby inhibiting proliferation and affecting cells with high turnover (19).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, several studies have indicated that oral aspirin is often selected as the initial treatment for postpericardiotomy syndrome, whereas additional steroids and colchicine are administered in refractory cases [2][3][4]. However, there is no consensus regarding the doses to be administered, administration methods, or durations.…”
Section: Introductionmentioning
confidence: 99%